"Stay away from them until you're old enough to make a decision": tobacco company testimony about youth smoking initiation. (27th November 2006) - Wakefield, Melanie; McLeod, Kim; Perry, Cheryl L
Abstract : Objective: To determine common themes used by US tobacco industry witnesses pertaining to youth smoking initiation during litigation in the United States. Methods: Qualitative thematic analysis of transcripts from 29 tobacco litigation cases dating from 1992 to 2002. Results: Youth smoking is portrayed by the tobacco industry as a source of great concern to them. Youth smoking prevention programmes developed by US tobacco companies are supposedly intended to delay decision-making about smoking until age 18, when individuals are then seen to be of an age where they are able to "choose to smoke". Tobacco industry media campaigns, youth access, community and school-based programmes are predicated on peer influence, parental factors, and commercial access being the primary influences on youth smoking uptake, rather than tobacco marketing, inaccurate risk appraisal, price and other factors known to influence youth smoking. Despite substantial financial investment in tobacco industry programmes, their witnesses were able to describe only weak evaluation methods, being preoccupied with measures of message comprehension, programme reach and uptake, and the associated costs of their efforts, rather than any evaluation designed to assess effects on youth smoking behaviour. Conclusion: Stated concerns about youth smoking and youth smoking prevention programmes are put forward in litigation as evidence that the tobacco industry is "serious" about tackling youth smoking, and serve as a primary strategy to improve the tobacco industry's public image. The tobacco industry's evaluation of the effectiveness of their youth smoking prevention programmes is demonstrably insufficient under current public health evaluation standards. Public health and welfare agencies should avoid engagement with tobacco industry-sponsored programmes.